Sociodemographic factors and their influence on school health and HIV programmes: the case of Lesotho - Letsie, Puleng Relebohile (University of the Free State, 2020)
Many adolescents and young people approach adulthood faced with conflicting and confusing messages about sexuality, gender, and culture. These are often exacerbated by embarrassment, reprimanding, silence, and disapproval of open discussion of sexual matters. These young people, often school-going, are affected by many challenges, and in various ways. Some of these challenges include HIV, high morbidity, premature deaths, orphan hood and early and unintended pregnancy (EUP), among other challenges. These are more pronounced in Lesotho, as the country has the second highest HIV prevalence globally. Moreover, they are exacerbated by the high levels of other communicable and non-communicable diseases, social inequalities, and economic challenges. The education sector is facing considerable challenges due to the high HIV prevalence among adolescents and youth, increasing levels of school-related gender-based violence, as well as the large number of teenage pregnancies among school-going adolescents and young people. In Lesotho, and in most countries in Southern Africa, young people are reported to have their sexual debut from as early as 12 years. School settings therefore provide an important opportunity to reach large numbers of young people with HIV prevention, treatment and impact mitigation programmes through integrated school health and Comprehensive Sexuality Education (CSE) programmes, offering an appropriate structure through the formal curriculum. Although the education sector has been responding to these challenges, glaring gaps continue to surface. These are mainly related to the social and cultural dynamics about educating young people about health, sex, sexuality, HIV and other social issues. Among the various sociodemographic factors, this study critically analyses how gender and culture specifically, affect and influence school health and HIV programmes, with a specific focus on comprehensive sexuality education (CSE) within schools. It highlights the key health issues and challenges, as well as other critical social issues facing adolescents. Furthermore, it continues to narrate the nature and scope of school-based health and HIV prevention programmes in Lesotho. It draws special attention to the relationship between sociodemographic factors and the education sector; and highlights how the selected sociodemographic factors influence and affect school health and HIV programmes, specifically sexuality education. It then concludes with recommending a culturally sensitive and gender transformative implementation framework that can be adopted to contextualise responses to the HIV epidemic and enhance CSE implementation, as it emphasises what is required for effective health and HIV programmes in schools. The findings revealed that the roles, attributes, behaviours, and level of comfort of parents / guardians and teachers highly affect the success of school health and sexuality education programmes. The curriculum content should be informed by prevalent, gender transformative and culturally sensitive materials and issues, with learners and communities also contributing to the development of the curriculum and strategies to roll it out. Emphasis is placed on the need for deeper and more meaningful content within the curriculum, as well as the continuous updating of key health topics, such as menstrual health management (MHM), which is a glaring gap in the current curriculum. Finally, for school health and sexuality education programmes to be effective, meaningful, and efficient, they should be implemented alongside youth-friendly health services. For them to have considerable impact, these programmes should look beyond the individual to the society, addressing not only safer sexual practices, but underlying contextual issues, such as gender inequality and culture. These factors include parental involvement in school-based health and HIV programmes; community involvement in the review of curricula; and stakeholder perceptions about the key issues around sexuality and related challenges.
Thesis (Ph.D. (Educational Psychology))--University of the Free State, 2020
Keywords: Adolescents; Comprehensive Sexuality Education; Culture; Gender; HIV; School Health; Sociodemographic factors